Genomic profiling of sporadic multiple meningiomas - E. Zeynep Erson-Omay; Shaurey Vetsa; Sagar Vasandani; Tanyeri Barak; Arushii Nadar; Neelan Marianayanam; Kanat Yalcin; Danielle Miyagishima; Stephanie Marie Aguilera; Stephanie Robert; Ketu Mishra-Gorur; Robert K. Fulbright; et al. (BMC, 2022)
Abstract Background Multiple meningiomas (MMs) rarely occur sporadically. It is unclear whether each individual tumor in a single patient behaves similarly. Moreover, the molecular mechanisms underlying the formation of sporadic MMs and clonal formation etiology of these tumors are poorly understood. Methods Patients with spatially separated MMs without prior radiation exposure or a family history who underwent surgical resection of at least two meningiomas were included. Unbiased, comprehensive next generation sequencing was performed, and relevant clinical data was analyzed. Results Fifteen meningiomas and one dural specimen from six patients were included. The majority of tumors (12/15) were WHO Grade I; one patient had bilateral MMs, one of which was Grade II, while the other was Grade I. We found 11/15 of our cohort specimens were of NF2-loss subtype. Meningiomas from 5/6 patients had a monoclonal origin, with the tumor from the remaining patient showing evidence for independent clonal formation. We identified a novel case of non-NF2 mutant MM with monoclonal etiology. MMs due to a monoclonal origin did not always display a homogenous genomic profile, but rather exhibited heterogeneity due to branching evolution. Conclusions Both NF2-loss and non-NF2 driven MMs can form due to monoclonal expansion and those tumors can acquire inter-tumoral heterogeneity through branched evolution. Grade I and II meningiomas can occur in the same patient. Thus, the molecular make-up and clinical behavior of one tumor in MMs, cannot reliably lend insight into that of the others and suggests the clinical management strategy for MMs should be tailored individually.